Willingness of Adults in the United States to Receive HIV Testing in Dental Care Settings: Cross-Sectional Web-Based Study - Rosso, Matthew T; Sharma, Akshay (JMIR Publications, 2020)
BackgroundThe Centers for Disease Control and Prevention estimates that 1.1 million people in the United States are living with HIV and 1 in 8 are estimated to be unaware of their serostatus. Little is known about whether individuals would consider being tested for HIV in nontraditional health care settings such as a dentist's office. Studies in selected US cities have indicated high acceptability of receiving an HIV test among people attending dental clinics. However, we are not aware of studies that have assessed willingness to receive HIV testing in dental care settings at a national level. ObjectiveUsing a web-based sample of adult residents of the United States, we sought to assess the self-reported willingness to receive any type of HIV testing (ie, oral fluid rapid testing, finger-stick blood rapid testing, or venipuncture blood testing) in a dental care setting and evaluate independent associations of willingness with the extent to which dental care providers were perceived as knowledgeable about HIV and how comfortable participants felt discussing HIV with their dental care providers. MethodsParticipants were recruited using banner advertisements featured on social networking platforms (Facebook and Instagram) from December 2018 to February 2019. Demographic and behavioral data including information on sexual behaviors in the past 6 months, HIV testing history, and dental/health care-seeking history were collected using an anonymous web-based survey. Willingness to receive any type of HIV testing in a dental care setting was assessed on 4-point scale from very willing to very unwilling. Factors independently associated with participants' willingness were identified using a multivariable logistic regression model. ResultsOf the 421 participants in our study aged 18 to 73 years, 271 (64.4%) reported having oral sex, 197 (46.8%) reported having vaginal sex, and 136 (32.3%) reported having anal sex in the past 6 months. Approximately one-third had never been tested for HIV (137/421, 32.5%), and the same proportion had not been tested in the past year (137/421, 32.5%). Most participants had dental insurance coverage (356/421, 84.6%), and more than three-fourths reported being very or somewhat willing (326/421, 77.4%) to receive any type of HIV testing in a dental care setting. Higher levels of willingness were associated with being 18 to 24 years versus ≥35 years (aOR 3.22, 95% CI 1.48-6.98), 25 to 34 years versus ≥35 years (aOR 5.26, 95% CI 2.52-10.98), believing that one's dental care provider is knowledgeable about HIV (aOR 2.04, 95% CI 1.06-3.92), and feeling comfortable discussing HIV with one's dental care provider (aOR 9.84, 95% CI 3.99-24.27). ConclusionsOur data indicate high acceptability of receiving HIV testing in a dental care setting, especially among those who report having a positive patient-provider relationship. Future research should focus on assessing dental care providers' attitudes, self-efficacy, and beliefs about whether HIV testing fits into the scope of dentistry.